PEMULUNG DI ERA MILENIAL - Jefriyanto, Candra (Jurnal Investasi Islam, 2019)
A scavenger is someone who works to collect used goods that can still be processed to become products that have resale value. Scavengers are always considered dirty, smelly, poor people. But it needs to be known to be more noble than having to beg without any effort to make ends meet. The challenge of globalization has made all levels of world society change massively towards a more sophisticated era of civilization. One of the products produced from globalization is social media. This research was conducted to ﬁ nd out how the scavenger life strategy and want to examine the extent to which scavengers wrestle with the challenges of globalization. This type of research used in this study uses a qualitative descriptive approach. Data sources obtained through interviews with informants numbered four people. The results showed that the level of scavenger education was very low, which was limited to elementary school. The shocking result was that none of the informants owned mobile phones and did not know the social media that was loved by the world community. The need for a good government role (good governance) to socialize social media and conduct skills-based training and education.